Perilaku Kedisiplinan Siswa Dilihat Dari Etika Belajar Di Dalam Kelas - Hilmi Mubarok Putra; deka - setiawan; nur - fajrie (Journal Prakarsa Paedagogia, 2020)
This study aims to determine student disciplinary behavior seen from the ethics of learning in the Karanganyar State Elementary School 2. The study was designed with a qualitative and descriptive approach in presenting research data. The approach used by researchers is a phenomenological approach with the consideration that this study seeks to describe the phenomenon of student disciplinary behavior seen from the ethics of learning in the classroom. The data can be in the form of interview transcripts, field data records, personal documents, photographs, and others. The subjects chosen were fifth grade students of SD Negeri Karangayar 2 district Demak. From the results of observations made by researchers as well as special notes showing the lack of discipline in student behavior. The results of this study can be used as additional insight into knowledge for readers in general, and at the same time as teacher improvement, especially in disciplined behavior seen from the ethics of learning in the classroom.